Alternative Strategy to Improve the Conservation of Javan Deer in Pangandaran Nature Reserve, West Java, Indonesia - Fahmi Idris Firdaus; Rina Ratnasih Irwanto; Elham Sumarga (Journal of Tropical Biodiversity and Biotechnology, 2023)
The habitat of Javan deer in Pangandaran Nature Reserve (PNR) faced natural changes, particularly due to the succession process of vegetation community in grazing areas, and inadequate infrastructures that affected the deer to roam outside PNR. This study aimed to formulate strategies for the conservation of Javan deer in PNR, focusing on ecological aspects and conservation management. The methods were encountering Javan deer individuals; scan sampling and continuous recording to observe the behaviour of Javan deer; calculating the productivity of grazing area by defoliation experiment and vegetation analysis; reviewing documents, reports and interviews; and analysing strategy using SWOT-QSPM. Results showed there were 43 Javan deer encountered roaming in PNR and outside the conservation area, and nine individuals gathered in Cikamal grassland. The productivity of the grazing areas (5.61 ha) was 93,826 kg of feed annually and was only sufficient for 23 individuals. The grazing areas were dominated by Cynodon dactylon. Javan deer spent their time feeding. Javan deer herd in Cikamal is more intolerant to humans compared to the herd in Pangandaran Nature Tourist Park (PNTP). This study recommends: considering the management status of Javan deer in the conservation management of PNR and PNTP; improving the conservation management of Javan deer and its habitat; improving facilities and the management system of those facilities and conservation-supporting infrastructures; collaboration with researchers to perform some research and innovations for Javan deer conservation; improving the capability of PNR staff theoretically and practically; and educating and empowering the local people in terms of Javan deer conservation.